Initial stiffness and plastic resistance of bolted stainless steel T-stubs in tension. (October 2020) - Yuan, H.X.; Gao, J.D.; Theofanous, M.; Yang, L.; Schafer, B.W.
Abstract: Building upon a previous investigation, this study reports a total of 13 experimental tests on austenitic and duplex stainless steel T-stubs subject to monotonic loading. The structural behaviour of the tested T-stub specimens, including load versus displacement ( F - Δ ) curves and corresponding failure modes, was obtained and is reported herein. The experimental tests were replicated by finite element (FE) analysis, and upon validation of numerical models, a comprehensive parametric study including 168 FE models was conducted to investigate the effects of key parameters such as material grade, bolt preloading, bolt diameter and flange thickness on the structural response. Based on both experimental and numerical results, the suitability of the design provisions for the determination of the plastic resistance specified in EN 1993-1-8, proposed extensions thereof by Demonceau et al. to cover T-stubs with four bolts per row for stainless steel T-stubs as well as the design method codified in Chinese code JGJ 82 were assessed. Novel design methods for the determination of the initial stiffness and the plastic resistance of stainless steel T-stubs, accounting explicitly for the observed structural response and the pronounced material strain hardening were developed. The proposed design methods lead to improved and more consistent capacity predictions and their adoption in design standards is recommended herein. Graphical abstract: Unlabelled Image Highlights: Thirteen monotonic loading tests on bolted stainless steel T-stubs in tension. FE models validated against available tests and parametric studies carried out. Calculation method for determination of the initial stiffness of stainless steel T-stubs. Newly proposed design method for predicting the plastic resistance of stainless steel T-stubs. Reliability analysis verifies the partial resistance factors of the proposed method.